2006
DOI: 10.1088/0029-5515/46/9/s09
|View full text |Cite
|
Sign up to set email alerts
|

Reflectometry measurements during operation of the dynamic ergodic divertor at TEXTOR

Abstract: The O-mode correlation reflectometer at TEXTOR is used for the investigation of the propagation and the properties of the turbulence at the plasma edge. The multi-horn antenna setup allows the investigation of the correlation properties of the turbulence and its rotation. Turbulence and plasma rotation for different plasma conditions are found to be in agreement and based on this comparison the radial electric field is estimated. In addition the density fluctuation level is estimated from the standard deviatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
22
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 31 publications
9
22
0
Order By: Relevance
“…The E r B shear rate is, however, reduced by the DED at all measured radial locations. Similar changes in E r were observed earlier on TEXT [13] and recently on TEXTOR by other diagnostics [14]. A possible explanation is that with ED the electrons move faster than massive ions along the field lines to the wall so that a positive E r must be created to restore the ambipolarity.…”
supporting
confidence: 81%
“…The E r B shear rate is, however, reduced by the DED at all measured radial locations. Similar changes in E r were observed earlier on TEXT [13] and recently on TEXTOR by other diagnostics [14]. A possible explanation is that with ED the electrons move faster than massive ions along the field lines to the wall so that a positive E r must be created to restore the ambipolarity.…”
supporting
confidence: 81%
“…If the GAM has a radial eigenmode structure then the spacing of adjacent plateaus maybe indicative of the mode half wavelength (cf. [29]). For the circular plasmas the radial wavelength would be λ r ∼ O(5 − 6) cm.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…It was previously suggested that the pedestal, or more specifically the second radial derivatives in the profiles, ∂ 2 /∂r 2 , may act as some form of barrier [11]. It is notable that most shaped devices report GAMs only within a few cm of the edge, while both the TEXT and TEXTOR circular devices have observed GAMs relatively deep in the plasma [16,39]. Unfortunately density profiles were not provided, but parabolic-like profiles are suspected, c.f.…”
Section: Gam Peak Splittingmentioning
confidence: 99%